Obstacle detection and avoidance system performed with drone using ROS and Python (ARPN journal of engineering and applied sciences, 2023)
The AR Drone 2.0 obstacle detection and avoidance system using ROS (Robot Operating System) as a development environment, OpenCV as a library for image processing, and Python as a programming language are presented. The algorithm is based on the object's color feature to determine whether it is an obstacle to allowing autonomous flights to the drone if the drone's battery charge level and its distance from the ground station are considered. The obstacle detection scenario is simulated using ROS-Gazebo, and then the algorithm is tested in a real controlled environment. It shows the proper functioning of the system, that is, it manages to detect a red object correctly and avoid it by the control actions implemented in the algorithm.